Interactions between PCSK9 and NLRP3 inflammasome signaling in atherosclerosis - Wang, Yanan; Fang, Dan; Yang, Qinzhi; You, Jingcan; Wang, Liqun; Wu, Jianbo; Zeng, Min; Luo, Mao (Frontiers in Immunology, 2023)
Atherosclerosis is an early pathological basis of numerous cardiovascular events that result in death or disability. Recent studies have described PCSK9 as a novel target for the treatment of atherosclerosis; PCSK9 is capable of degrading LDLR on the surface of hepatocytes through the regulation of lipid metabolism, and it can function as a novel inflammatory modulator in atherosclerosis. Inflammasomes are important intracellular multiprotein complexes that promote the inflammatory response in atherosclerosis. Among inflammasomes, the NLRP3 inflammasome is particularly notable because of its important role in the development of atherosclerotic disease. After activation, NLRP3 forms a complex with ASC and pro-caspase-1, converting pro-caspase-1 into activated caspase-1, which may trigger the release of IL-1β and IL-18 and contribute to the inflammatory response. Several recent studies have indicated that there may be interactions between PCSK9 and the NLRP3 inflammasome, which may contribute to the inflammatory response that drives atherosclerosis development and progression. On the one hand, the NLRP3 inflammasome plays an important role via IL-1β in regulating PCSK9 secretion. On the other hand, PCSK9 regulates caspase-1-dependent pyroptosis by initiating mtDNA damage and activating NLRP3 inflammasome signaling. This paper reviews the mechanisms underlying PCSK9 and NLRP3 inflammasome activation in the context of atherosclerosis. Furthermore, we describe the current understanding of the specific molecular mechanism underlying the interactions between PCSK9 and NLRP3 inflammasome signaling as well as the drug repositioning events that influence vascular cells and exert beneficial antiatherosclerotic effects. This review may provide a new therapeutic direction for the effective prevention and treatment of atherosclerosis in the clinic